O uso de plantas medicinais nas comunidades do entorno do Parque Nacional da Serra de Itabaiana/SE : a (des/re) construção do saber tradicional - Botelli, ângelo Augusto Kohnert (2010)
This dissertation aims to study the villages of Bom Jardim and Mundês. The two villages are located in the vicinity of the National Park of Itabaiana / SE. The study was motivated by an interest in investigating the process of (de / re) construct of socio-cultural characteristics among young people about traditional knowledge regarding the use of medicinal plants for treating common sickness of everyday life. The main variable under investigation is the involvement of health workers in villages, through which western medicine can contribute to reducing child mortality and health care of residents of these villages, but at the same time, result in the loss of traditional knowledge in new generations in relation to knowledge of the uses of medicinal plants. The methodology provides for the identification of "guardians of nature" (Giddens) of these villages through the technique snowball . The network of informants will limit the principle of saturation point. The first step of the research was given towards the lifting of secondary data at the Secretaria Municipal de Itabaiana / SE, for the preparation of a guide to be developed from interviews with health workers. Based on literature (Ennes, 2008), it was found that most villagers in case of illness, looking for health clinics and hospitals and there are almost no villagers and those looking for more traditional forms of healing. This has been confronted by the field work has identified three guardians in Bom Jardim and ten guardians in Mundês, where all reported that they have people interested in your knowledge, are family members or young people in the villages.